The Ritual Agency and Living Tradition of Aḍ-Ḍamm ‘Alā Qalb al-Qur’ān in Local Islamic Communities of Banyumas - Sobirin, Mohamad (UIN Sunan Kalijaga Yogyakarta, 2025)
This ethnographic research investigates the living tradition and protective belief (tolak bala’) associated with the Aḍ-Ḍamm ‘Alā Qalb al-Qur’ān manuscripts preserved in two pesantren mosques in Banyumas, Central Java, i.e., Al-Djazuli Pliken and Pasulukan Sokaraja Lor. Local Muslim communities believe that possessing or storing these sacred manuscripts safeguards individuals, households, and places of worship from disasters, particularly fire. Over time, this belief has transformed from an individual conviction into an institutionalized communal practice, representing an intersection of Islamic textual reverence and localized ritual protection. Distinct from prior studies that focus primarily on textual content or codicological features, this study emphasizes the material, social, and symbolic dimensions of these manuscripts as active agents within local religious life. Drawing on in-depth interviews, participant observation, and narrative analysis, this research demonstrates how these manuscripts function simultaneously as sacred texts, material amulets, and markers of Islamic identity. Theoretically, this study contributes to debates on the materiality of sacred texts, folk belief systems, and the construction of ritual protection within localized Islamic traditions. The findings illustrate how Penginyongan Muslim communities in Banyumas embody and sustain a living tradition in which Islamic manuscripts transcend their textual function and are integrated into everyday practices of spiritual protection. This localized synthesis of belief, ritual, and manuscript materiality offers new insights into the interplay between Islam, culture, and protective traditions in Southeast Asian Muslim societies.